Preparation method and additive of electrolytic copper foil for lithium-ion battery with high bending resistance
By improving the preparation method of electrolytic copper foil of lithium-ion batteries, including wire drawing annealing and adding specific additives, the problem of insufficient bending resistance of existing electrolytic copper foils is solved, and the energy density and cycling performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202110598244.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-05-31
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-05-31
AI Technical Summary
The bending resistance of the electrolytic copper foil of existing lithium-ion batteries is not good enough, which leads to the wrinkling deformation of the diaphragm and pole sheet during the winding process, affecting the energy density and cycling performance of the battery.
A preparation method is adopted, including brushing annealing of the cathode copper raw material, forming copper oxide and reacting with dilute sulfuric acid to form copper sulfate, preparing an electrolyte, and adding bisbenzenesulfonylimide, fish glue, polypropylene glycol, dextrin and sodium dimethylformamide propane sulfonate as additives to form a grown foil by electrodeposition.
The bending resistance of electrolytic copper foil is improved, making it less likely to cause mechanical fracture when bending, significantly improving the energy density and circulation performance of the battery, while reducing safety hazards.
Smart Images

Figure CN115478305B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrolytic copper foil preparation, and in particular to a method for preparing electrolytic copper foil for lithium ion batteries with high bending resistance. Background Art
[0002] Due to the complex characteristics of the wound battery structure, there are multiple bends and thickness change areas in the length direction of the entire pole piece. Especially in the small-angle bend area near the middle of the core and the collector welding area, due to the uneven winding tension and shape changes, it is easy to cause the diaphragm and the pole piece to wrinkle and deform, and the positive and negative electrodes cannot get effective contact, resulting in a reaction dead zone. During charging, "lithium precipitation" is prone to occur at the edges of the wrinkles, causing the effective active substances of the battery to not fully react, reducing the battery energy density and the battery cycle performance, and also causing great safety hazards. As the negative electrode current collector of lithium-ion batteries, the bending resistance of copper foil has a huge impact on the winding manufacturing process of the negative electrode of lithium-ion batteries. At the same time, wound batteries require copper foil to have better folding resistance. Therefore, studying how to obtain electrolytic copper foil with high bending resistance for lithium-ion batteries has become an urgent problem to be solved in the lithium-ion battery industry. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a method for preparing electrolytic copper foil for lithium ion batteries with a relatively simple implementation process, relatively mild preparation conditions and good bending resistance and an additive thereof in view of the defect that the existing electrolytic copper foil for lithium ion batteries has poor bending resistance.
[0004] In order to solve the above technical problems, the present invention adopts the following technical solution: a method for preparing an electrolytic copper foil for lithium-ion batteries with high bending resistance, characterized in that the method is carried out according to the following steps:
[0005] 1) The cathode copper raw material is subjected to wire drawing annealing treatment: first, the A-grade copper raw material is added to the melting furnace to melt into copper liquid, and inert gas protection is adopted, and the inert gas plays a deoxidation role; the copper liquid is purified in the transition chamber and then introduced into a crystallizer with cooling water through a heat preservation furnace for cooling and crystallization, and the oxygen-free copper rods of 7-9 mm are continuously drawn out, and the drawn copper rods are taken up and loaded into a reel by a take-up device;
[0006] 2) The copper rod is then drawn into a 2.5-3.5 mm copper wire through a wire drawing die using a copper drawing machine, and then baked in a high-temperature sealed furnace and taken out;
[0007] 3) Copper dissolving and liquid making: copper wire is placed in a copper dissolving tank to react and generate copper oxide, which then quickly reacts with dilute sulfuric acid to generate copper sulfate to obtain an electrolyte;
[0008] 4) supplying the electrolyte to the high-level tank, adding the prepared additives and chloride ions to the high-level tank, mixing the additives, chloride ions and electrolyte evenly and then supplying them to the foil production process;
[0009] 5) Raw foil manufacturing: The electrolyte supplied by the high-level tank is transported to the electrolytic cell through the liquid inlet pipe of the raw foil machine for electrodeposition to form raw foil. By controlling the cathode rotation line speed, winding tension and other process indicators (such as line speed of 2-8m / min, winding tension of 150-300N), copper foil of target thickness (such as 6μm, 8μm, 9μm) is produced;
[0010] The raw material components of the additive added in step 4) include bisbenzenesulfonimide, fish glue, polypropylene glycol, dextrin and sodium dimethylformamidopropane sulfonate.
[0011] The temperature of the molten copper is maintained at 1140°C-1160°C when passing through the holding furnace.
[0012] The copper rod is drawn into copper wire by a copper drawing machine through a set of wire drawing dies from large to small, and then baked in a sealed furnace at a temperature of 700°C for 3 hours and taken out to ensure that the purity of the processed copper wire is ≥99.99%.
[0013] Before the electrolyte enters the high-level tank, impurities are removed through a purification process, that is, 200-mesh coconut shell activated carbon is used to adsorb organic impurities, and a multi-stage filtration method is used to gradually filter and remove particles from large to small, ensuring that the filtration accuracy is within 0.5 microns.
[0014] The process parameters of the preparation process are as follows: Cu 2+ The content is 90-110g / L, H 2 SO 4 The content is 95-115g / L, Cl - The concentration is 25-35ppm, the electrolyte temperature is 48-54℃, and the liquid volume is 48-52m 3 / h, the current intensity of the foil production section is controlled at 25KA-35KA.
[0015] In the copper dissolving tank, the copper wire reacts with oxygen or dissolved oxygen to form copper oxide.
[0016] An additive for preparing the electrolytic copper foil for lithium-ion batteries with high bending resistance, characterized in that: its raw material components include bisbenzenesulfonimide, fish glue, polypropylene glycol, dextrin and sodium dimethylformamidopropane sulfonate, wherein the content of bisbenzenesulfonimide is 0.4-0.8 g / L, the content of fish glue is 8-12 g / L, the content of polypropylene glycol is 1.8-2.2 g / L, the content of dextrin is 0.3-0.8 g / L, and the content of sodium dimethylformamidopropane sulfonate is 6-10 g / L; bisbenzenesulfonimide, fish glue, polypropylene glycol, dextrin and sodium dimethylformamidopropane sulfonate are prepared into an aqueous solution in proportion.
[0017] Preferably, the content of each raw material is 0.6 g / L of bisbenzenesulfonimide, 10 g / L of fish glue, 2 g / L of polypropylene glycol, 0.5 g / L of dextrin, and 8 g / L of sodium dimethylformamidopropane sulfonate.
[0018] The present invention can achieve good leveling effect by adding bisbenzenesulfonimide to the electrolyte; fish glue and Cu 2+ Can complex, so that Cu 2+ It is difficult to get electrons, thus hindering Cu 2+ Rapid deposition on the cathode roller increases the growth points of copper on the cathode roller, making the crystal nuclei of the electrolytic copper foil more uniform. Polypropylene glycol can enhance the cathode polarization of the electrolyte, improve the leveling and wetting properties of the coating, and make the copper foil grains formed by electrolysis more uniform, fine and compact; dextrin will increase the cathode polarization, hinder the reduction of copper ions and the growth of crystals; sodium dimethylformamidopropane sulfonate plays a role in grain refinement and preventing high-area scorching. The grains of the copper foil prepared using the above composite additives are small and evenly distributed. Such a grain structure is not easy to propagate cracks at the grain interface when the copper foil is bent, and it is not easy to mechanically fracture, so it has excellent bending resistance.
[0019] After the raw copper material is purified and the electrolyte is purified, the microstructure morphology of 6μm, 8μm and 9μm copper foils prepared by adding the additive of the present invention is flat and smooth, and the bending resistance is greatly improved compared with the copper foil prepared by adding the conventional additive process. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The present invention is a process flow chart for preparing the same;
[0021] Figure 2 This is a SEM picture of the 9μm electrolytic copper foil prepared by the present invention, with the left side being the smooth side and the right side being the matte side;
[0022] Figure 3 This is a SEM picture of the 8μm electrolytic copper foil prepared by the present invention, with the left side being the smooth side and the right side being the matte side;
[0023] Figure 4This is a SEM picture of the 6 μm electrolytic copper foil prepared in the present invention, with the left side being the smooth side and the right side being the matte side. DETAILED DESCRIPTION
[0024] The following is combined with Figure 1 The present invention is further described by specific embodiments:
[0025] In this embodiment, the method for preparing the electrolytic copper foil for lithium-ion batteries with high bending resistance is carried out according to the following steps:
[0026] 1) Wire drawing annealing treatment is performed on the cathode copper raw material: first, the A-grade copper raw material is added to the melting furnace to melt into copper liquid, and inert gas is used for protection. The copper liquid is purified in the transition chamber and then introduced into a crystallizer with cooling water through a heat preservation furnace for cooling and crystallization, and the oxygen-free copper rods of 7-9 mm (such as 8 mm) are continuously drawn out, and the drawn copper rods are wound up and loaded into a reel by a wire-taking device;
[0027] 2) The copper rod is then drawn into a copper wire of 2.5-3.5 mm (such as 3 mm) by a copper drawing machine through a wire drawing die, and then baked in a high-temperature sealed furnace and taken out;
[0028] 3) Copper dissolving and liquid making: copper wire is placed in a copper dissolving tank to react and generate copper oxide, which then quickly reacts with dilute sulfuric acid to generate copper sulfate to obtain an electrolyte;
[0029] 4) supplying the electrolyte to the high-level tank, adding the prepared additives and chloride ions to the high-level tank, mixing the additives, chloride ions and electrolyte evenly and then supplying them to the foil production process;
[0030] 5) Raw foil manufacturing: The electrolyte supplied by the high-level tank is transported to the electrolytic cell through the liquid inlet pipe of the raw foil machine for electrodeposition to form raw foil. By controlling the cathode rotation line speed, winding tension and other process indicators (such as line speed of 2-8m / min, winding tension of 150-300N), copper foil with target thickness of 6μm, 8μm and 9μm is produced;
[0031] The raw material components of the additive added in step 4) include bisbenzenesulfonimide, fish glue, polypropylene glycol, dextrin and sodium dimethylformamidopropane sulfonate.
[0032] In step 1), the melting furnace is filled with an inert gas for deoxidation.
[0033] The temperature of the molten copper is maintained at 1140°C-1160°C when passing through the holding furnace.
[0034] The copper rod is drawn into copper wire by a copper drawing machine through a set of wire drawing dies from large to small, and then baked in a sealed furnace at a temperature of 700°C for 3 hours and taken out to ensure that the purity of the processed copper wire is ≥99.99%.
[0035] Before the electrolyte enters the high-level tank, impurities are removed through a purification process, that is, 200-mesh coconut shell activated carbon is used to adsorb organic impurities, and a multi-stage filtration method is used to gradually filter and remove particles from large to small, ensuring that the filtration accuracy is within 0.5 microns.
[0036] The process parameters of the preparation process are as follows: Cu 2+ The content is 90-110g / L, H 2 SO 4 The content is 95-115g / L, Cl - The concentration is 25-30ppm, the electrolyte temperature is 48±54℃, and the liquid volume is 48-52m 3 / h, the current intensity of the foil production section is controlled at 25KA-35KA.
[0037] In the copper dissolving tank, the copper wire reacts with oxygen or dissolved oxygen to form copper oxide.
[0038] The additive for preparing the electrolytic copper foil for lithium-ion batteries with high bending resistance mentioned above comprises raw materials including bisbenzenesulfonimide, fish glue, polypropylene glycol, dextrin and sodium dimethylformamidopropane sulfonate, and the content of each raw material is 0.6 g / L of bisbenzenesulfonimide, 10 g / L of fish glue, 2 g / L of polypropylene glycol, 0.5 g / L of dextrin and 8 g / L of sodium dimethylformamidopropane sulfonate; bisbenzenesulfonimide, fish glue, polypropylene glycol, dextrin and sodium dimethylformamidopropane sulfonate are prepared into an aqueous solution in proportion.
[0039] Test method for bending resistance:
[0040] After testing, the bending resistance performance results of the copper foil of this embodiment are as follows:
[0041]
[0042] The bending resistance of copper foil prepared using conventional additive component 1 (sodium polydisulfide propane sulfonate 15 g / L, polyethylene glycol 12 g / L, collagen 5 g / L) is as follows:
[0043]
[0044] The bending resistance of copper foil prepared using conventional additive component 2 (12 g / L sodium polydisulfide propane sulfonate, 0.2 g / L hydroxyethyl cellulose, 28 g / L collagen, 0.5 g / L sodium N,N-dimethyl-dithiocarboxamide propane sulfonate) is as follows:
[0045]
[0046] The bending resistance of copper foil prepared using conventional additive component 3 (30 g / L sodium polydisulfide propane sulfonate, 24 g / L polyethylene glycol, 28 g / L collagen, 0.5 g / L sodium N,N-dimethyl-dithiocarboxamide propane sulfonate) is as follows:
[0047]
[0048] After the raw copper material is purified and the electrolyte is purified, the microstructure morphology of 6μm, 8μm and 9μm copper foils prepared by adding the additive of the present invention is flat and smooth, and the bending resistance is greatly improved compared with the copper foil prepared by adding the conventional additive process.
[0049] The present invention has been described in detail above. The above description is only a preferred embodiment of the present invention and should not limit the scope of implementation of the present invention. That is, all equivalent changes and modifications made within the scope of this application should still fall within the scope of the present invention.
Claims
1. A method for preparing an electrolytic copper foil for lithium-ion batteries with high bending resistance, characterized in that: Follow the steps below, 1) Wire drawing annealing treatment of cathode copper raw materials: first, add grade A copper raw materials into a melting furnace to melt into copper liquid, and use inert gas protection. After purification in the transition chamber, the copper liquid is introduced into a crystallizer with cooling water through a heat preservation furnace for cooling and crystallization, and the oxygen-free copper rods of 7-9 mm are continuously drawn out, and the drawn copper rods are wound up and loaded into a reel through a wire-taking device; 2) The copper rod is then drawn into 2.5-3.5 mm copper wire through a wire drawing die using a copper drawing machine, and then baked in a high-temperature sealed furnace and taken out; 3) Copper dissolving and liquid making: copper wire is placed in a copper dissolving tank to react and generate copper oxide, which then quickly reacts with dilute sulfuric acid to generate copper sulfate to obtain an electrolyte; 4) The electrolyte is supplied to the high-level tank, and the prepared additives and chloride ions are added to the high-level tank. The additives, chloride ions and electrolyte are mixed evenly and then supplied to the foil production process; 5) Raw foil manufacturing: The electrolyte supplied by the high-level tank is transported to the electrolytic cell through the liquid inlet pipe of the raw foil machine for electrodeposition to form raw foil, producing copper foil of target thickness; Among them, the raw material components of the additive added in step 4) include bisbenzenesulfonimide, fish glue, polypropylene glycol, dextrin and sodium dimethylformamidopropane sulfonate, the bisbenzenesulfonimide content is 0.4-0.8 g / L, the fish glue content is 8-12 g / L, the polypropylene glycol content is 1.8-2.2 g / L, the dextrin content is 0.3-0.8 g / L, and the sodium dimethylformamidopropane sulfonate content is 6-10 g / L.
2. The method for preparing the electrolytic copper foil for lithium ion battery with high bending resistance according to claim 1, characterized in that: In step 1), an inert gas is filled into the melting furnace to perform a deoxidation function.
3. The method for preparing the electrolytic copper foil for lithium ion battery with high bending resistance according to claim 1, characterized in that: The temperature of the molten copper is maintained at 1140°C-1160°C when passing through the holding furnace.
4. The method for preparing the electrolytic copper foil for lithium ion battery with high bending resistance according to claim 1, characterized in that: The copper rod is drawn into copper wire by a copper drawing machine through a set of wire drawing dies from large to small, and then baked in a sealed furnace at a temperature of 700 ℃ for 3 hours and taken out to ensure that the purity of the processed copper wire is ≥99.99%.
5. The method for preparing the electrolytic copper foil for lithium ion battery with high bending resistance according to claim 1, characterized in that: Before the electrolyte enters the high-level tank, impurities are removed through a purification process, that is, 200-mesh coconut shell activated carbon is used to adsorb organic impurities, and a multi-stage filtration method is used to gradually filter and remove particles from large to small, ensuring that the filtration accuracy is within 0.5 microns.
6. The method for preparing the electrolytic copper foil for lithium ion battery with high bending resistance according to claim 1, characterized in that: The process parameters of the preparation process are as follows: Cu2+ content is 90-110g / L, H2SO4 content is 95-115g / L, Cl- concentration is 25-35ppm, electrolyte temperature is 48-54℃, and liquid inlet volume is 48-52m 3 / h, the current intensity of the foil production section is controlled at 25 KA-35KA.
7. The method for preparing the electrolytic copper foil for lithium ion battery with high bending resistance according to claim 1, characterized in that: In the copper dissolving tank, the copper wire reacts with oxygen or dissolved oxygen to form copper oxide.
8. An additive for preparing electrolytic copper foil for lithium ion batteries with high bending resistance according to claim 1, characterized in that: The raw material components include bisbenzenesulfonimide, fish glue, polypropylene glycol, dextrin and sodium dimethylformamidopropane sulfonate, wherein the content of bisbenzenesulfonimide is 0.4-0.8 g / L, the content of fish glue is 8-12 g / L, the content of polypropylene glycol is 1.8-2.2 g / L, the content of dextrin is 0.3-0.8 g / L, and the content of sodium dimethylformamidopropane sulfonate is 6-10 g / L; bisbenzenesulfonimide, fish glue, polypropylene glycol, dextrin and sodium dimethylformamidopropane sulfonate are prepared into an aqueous solution according to proportion.
9. The additive for preparing electrolytic copper foil for lithium ion battery with high bending resistance according to claim 8, characterized in that: The content of each raw material is as follows: 0.6 g / L of bisbenzenesulfonimide, 10 g / L of isinglass, 2 g / L of polypropylene glycol, 0.5 g / L of dextrin, and 8 g / L of sodium dimethylformamidopropanesulfonate.
Citation Information
Patent Citations
Preparation method of high-performance electrolytic copper foil
CN103132110A
Additive for electrolytic copper foil, and production technique of electrolytic copper foil
CN103276416A